Comparative study of planning history, spatial development and sociological significance of the back alley in Yangon and Singapore - Matsushita, Tomoko; Meguro, Kimiro; Kubota, Aya (International Planning History Society Proceedings, 2018)
A comparison of two similar types of back alley spaces: Back Drainage Space (BDS) in Yangon and Back-lane in Singapore, is conducted to find out if there are any relationships between their spatial development and lessons that can be learned from the precedent case in Singapore. Commonalities and differences of the back alley are identified by comparing the historical urban context of their formation and development in British colonial cities. The findings suggest that the back alley spaces in both cities, despite divergent circumstances and development after independence, possess common traits as interstitial space between public and private, with a unique way of spatial management based on informal, mutual agreement, which suggests some useful ideas when considering the role of these spaces in the redevelopment of Yangon in the near future.